2005
DOI: 10.1097/01.ccm.0000171840.01892.36
|View full text |Cite
|
Sign up to set email alerts
|

Early hypocalcemia in severe trauma*

Abstract: Hypocalcemia frequently occurs on arrival at the hospital in severe trauma patients, and colloid-induced hemodilution and severe shock and/or ischemia-reperfusion appear to be important causative factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 31 publications
8
77
2
4
Order By: Relevance
“…It has been shown that acidosis affects clot fi rmness and is not restored by sodium bicarbonate infusion (Martini et al 2006 ). Calcium is further depleted by the transfusion of citrate containing allogeneic blood products (Vivien et al 2005 ). Hence, acidosis, hypothermia, and hypocalcaemia must be avoided and treated at all times.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…It has been shown that acidosis affects clot fi rmness and is not restored by sodium bicarbonate infusion (Martini et al 2006 ). Calcium is further depleted by the transfusion of citrate containing allogeneic blood products (Vivien et al 2005 ). Hence, acidosis, hypothermia, and hypocalcaemia must be avoided and treated at all times.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…• l'hypocalcémie favorisée par la transfusion [20] ; • l'hypothermie (bloc opératoire, polytraumatisé en exté-rieur…).…”
Section: Hémostaseunclassified
“…Le diagnostic d'hypocalcémie se fait sur la calcémie ionisée (< 1,15 mmol/l), désormais facilement accessible grâce aux appareils de mesure des gaz du sang. La profondeur de l'hypocalcémie est corrélée de façon indépendante à la gravité des patients, à l'acidose et au volume de soluté colloïde administré dans une série de 212 patients polytraumatisés [16]. Le calcium est un coenzyme indispensable au fonctionnement de la majorité des enzymes de la coagulation de type protéase à sérine.…”
Section: Hypocalcémieunclassified